2018
DOI: 10.3389/fpsyt.2018.00187
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Acceptability of Interventions for Attenuated Positive Psychotic Symptoms in Individuals at Clinical High Risk of Psychosis: A Network Meta-Analysis

Abstract: Background: Attenuated positive psychotic symptoms represent the defining features of the clinical high-risk for psychosis (CHR-P) criteria. The effectiveness of each available treatment for reducing attenuated positive psychotic symptoms remains undetermined. This network meta-analysis (NMA) investigates the consistency and magnitude of the effects of treatments on attenuated positive psychotic symptoms in CHR-P individuals, weighting the findings for acceptability.Methods: Web of Science (MEDLINE), PsycInfo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 89 publications
1
94
1
4
Order By: Relevance
“…Two independent aggregate-data network meta-analyses published in 2018 found lack of evidence to favor specific preventive treatments compared to each (and every) other for improving attenuated positive psychotic symptoms (58,61).…”
Section: Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two independent aggregate-data network meta-analyses published in 2018 found lack of evidence to favor specific preventive treatments compared to each (and every) other for improving attenuated positive psychotic symptoms (58,61).…”
Section: Symptomsmentioning
confidence: 99%
“…Importantly, although the meta-analyses presented in Table 2 were conducted by different and independent research teams, their results converge. For example, two independent meta-analyses both concluded that there is no evidence to favor specific treatments over each other for improving attenuated positive psychotic symptoms in CHR-P individuals (58,61). Unfortunately, there is no robust evidence that current treatments can improve functional levels in these patients.…”
Section: Evidence-based Efficacy Of Preventive Treatments For Chr-p Imentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention of psychosis in patients at CHR-P and amelioration of symptoms are clinical priorities. However, there are currently no licensed pharmacological treatments for this patient group, which remains an unmet clinical need (Davies et al, 2018a(Davies et al, , 2018b. One potential novel treatment is the neuropeptide oxytocin, which is currently under investigation in relation to a number of neuropsychiatric disorders characterised by social dysfunction, such as autism spectrum disorder and schizophrenia.…”
Section: <Figure 1>mentioning
confidence: 99%